Technologies to produce liquid biofuels for transportation: An overview - Schwaiger, H.; Pena, N.; Mayer, A.; Bird, D.N. (Center for International Forestry Research, 2011)
This report provides an overview of the state of the art of first and second generation biofuel production pathways. Information is provided on primary feedstocks, typical feedstock yields, available conversion technologies, biofuel production costs and market opportunities. In this report, a pathway element is considered first generation if it is deployed at commercial scale. Thus corn, sugarcane, oil palm, and soya are first generation feedstocks, whereas jatropha is a second generation feedstock. Conversion technologies are similarly divided into first and second generation according to their level of deployment. Preferred feedstock production systems depend on country or regional circumstances. Factors such as climate and soils, marketing opportunities, traditional crop and land uses, and local production costs determine preferred biofuel production pathways. Currently the primary feedstocks for ethanol are corn and sugarcane, whereas soya, rapeseed and oil palm are the primary feedstocks used for biodiesel production. The easiest and lowest greenhouse gas (GHG) production path to ethanol is fermentation of sugarcane. Converting corn or similar starches into ethanol is more complex, because the raw material has to be converted to sugar prior fermentation. These pathways also tend to result in higher GHG emissions. Conversion of plant oils to biodiesel is primarily done via transesterification. Conversion of lignocellulosic materials (woodchips, straw, algae etc.) to ethanol or biodiesel requires second generation conversion technologies. Thermochemical processes can be used to convert these feedstocks into biodiesel (e.g., via Fischer-Tropsch processes), or enzymatic hydrolysis can be used to produce bioethanol. Currently ethanol from sugarcane is the only biofuel that is cost-competitive with fossil-based transportation fuels. Both biodiesel via transesterification and biofuels produced via second generation conversion processes have high production costs and need subsidies or higher fossil fuel prices to be competitive. Although export of biofuels could be a source of income for developing countries, trade in biofuels is expected to remain a small fraction of total biofuel production.